Strategi Guru dalam Membentuk Karakter Peduli Lingkungan Siswa: Teacher Strategies in Forming Students' Environmentally Caring Character - Apriana, Dewi; Rojali, Ahmad (STAI Publisistik Thawalib Jakarta, 2024)
The study seeks to identify the approaches and factors, both supportive and hindering, utilized by teachers in fostering a compassionate ethos at MI Ash Shiddiqiyah. Employing qualitative descriptive research, the author draws upon school principals, teachers, and students as data sources. Data gathering methods encompass observation, interviews, and documentation. Data analysis involves the reduction of information, presentation of findings, and drawing conclusions. The results of the research show that the teacher strategy used is implementing activities that must be carried out daily so that it becomes a habit, such as cleaning every morning, in addition to providing sufficient cleaning tools, providing insight into the importance of caring for environmental cleanliness which is integrated into the learning process, providing motivation. , appreciation, and good example by teachers. The supporting factor in forming this character is that teachers receive a lot of support from the school principal and the school committee. Apart from supporting factors, there are inhibiting factors in this process, namely the lack of availability of clean water supplies. The conclusion is that the strategies used by teachers are quite varied and continue to be implemented and even improved in protecting the environment.